Chemoprofiling of Active n-Hexane Fraction as Alpha-Glucosidase Inhibitors from Kanunang (Cordia myxa L.) Leaves from Enrekang South Sulawesi - Ahmad Najib (Journal of Global Pharma Technology, 2016)
Kanunang (Cordia myxa L.) is a native plant from tropical Asia. This study aims to determine the profile of chemical compounds contained in leaves of Kanunang (Cordia myxa) which can inhibit alpha-glucosidase enzyme. Extraction of Kanunang leaves was done by maceration method using ethanol 96% solvent for 3 days then filtered and thickened with rotary vacuum evaporator. Resulting extract with yield value of 5%. The extract was fractionated using conventional column method with n-hexane: ethyl acetate (10: 0) eluent. The n-hexane fraction was tested using the GC-MS instrument with the following condition; injector temperature 250°C, initial oven temperature 70°C, up to 325°C increasing 10°C/minute. The results obtained was 24 compounds which have alpha-glucosidase enzyme inhibitors activity with maximum abundance at RT 12:43, as 9,12,15-Octadecatrienoic Acid, methyl ester (C19H32O2) compound.Keywords: Cordia myxa L.; Chemical profile; GC-MS; Alpha-glucosidase.